Analisis Kekuatan Impak Material Komposit Berpenguat Serat Alam Bambu Petung Dengan Variasi Fraksi Volume - Salo, Lery Alfriany; Ramba, Dina (Riviera Publishing, 2025)
This research has an urgency to develop environmentally friendly materials as an alternative to synthetic fiber-based composite materials that are widely used in the automotive, construction, and manufacturing industries. This research develops bamboo fiber-based composites that have advantages such as corrosion resistance, lightweight, inexpensive, and competitive in strength with metal materials. The goal of this development is to produce a lightweight, strong, and elastic material, which can be applied to a variety of products. The composite sample was made using an epoxy resin matrix using the hand lay-up method. Three variations of fiber volume fractions (10%, 20%, and 30%) were used to explore their effect on load distribution and energy absorption ability during impact. The results showed the highest value of 0.552 J/mm2 at Sp30.6, which was a fiber volume fraction of 30%, while the lowest value at Sp10.4 was a 30% volume fraction of 0.0251J/mm2. This shows that the increase in the volume fraction of petung bamboo fibers in the epoxy matrix significantly increases the impact toughness of the composite. This research is expected to determine the optimal composition to produce the best impact strength, so it is expected to produce an ideal material configuration for sustainable industrial applications.